Studi Empiris: Pengaruh Produk, Kualitas Layanan, dan Harga terhadap Kepuasan Pelanggan Grab di Kota Purwodadi - Irfanda, Fakhri (Faculty of Economics and Business Universitas Dian Nuswantoro, 2024)
Advancements in information technology, particularly towards the globalization of communication, have a significant impact on the dynamics of society and the nation. The rapid development of information technology in recent years has brought both positive and negative effects on the lives of people across various countries. In Indonesia, the transportation sector is witnessing a transformation with the rise of application-based services, commonly referred to as online transportation. By delivering value and satisfaction to customers through competitive pricing of products and services, PT. Grab Indonesia has been motivated to enhance its application offerings, including GrabTaxi, GrabCar, GrabShare, GrabBike, GrabExpress, GrabFood, GrabHitch, and GrabHitch Car. Grab stands out as one of the largest online transportation platforms, with its market share fluctuating between 2019 and 2021. In 2019, Grab's market share was 43.1%, which increased to 43.5% in 2020, but subsequently declined to 39.7% in 2021. This success as a top brand is attributed to effective collaboration among management, drivers, and customers. By emphasizing comfort and safety, as well as maintaining competitive fares, Grab has been able to enhance its service ratings. To maintain its position as a leading brand, Grab must continually refine its strategies to attract public interest, demonstrate distinct advantages, and differentiate itself from competitors. Perkembangan teknologi informasi yang menuju globalisasi komunikasi memiliki dampak signifikan terhadap peradaban masyarakat dan bangsa. Saat ini, kita menyaksikan kemajuan pesat dalam teknologi informasi yang membawa berbagai konsekuensi, baik positif maupun negatif, terhadap kehidupan sosial di berbagai negara. Di Indonesia, sektor transportasi tengah mengalami transformasi dengan munculnya layanan berbasis aplikasi, yang dikenal sebagai transportasi online. Layanan ini menawarkan nilai tambah dan kepuasan kepada pelanggan melalui penyampaian produk dan jasa dengan harga kompetitif. PT. Grab Indonesia, sebagai salah satu pelaku utama, telah mengembangkan berbagai layanan aplikasi, termasuk GrabTaxi, GrabCar, GrabShare, GrabBike, GrabExpress, GrabFood, GrabHitch Bike, dan GrabHitch Car. Grab telah menjadi salah satu penyedia transportasi online terbesar di Indonesia, meskipun mengalami fluktuasi pangsa pasar antara tahun 2019 dan 2021. Pada tahun 2019, pangsa pasar Grab tercatat sebesar 43,1%, meningkat menjadi 43,5% pada tahun 2020, namun turun menjadi 39,7% pada tahun 2021. Keberhasilan Grab dalam meraih posisi top brand merupakan hasil dari kolaborasi yang baik antara manajemen, driver, dan konsumen. Dengan fokus pada kenyamanan dan keamanan, tarif juga berperan penting dalam mendukung reputasi layanan ini. Untuk mempertahankan status sebagai top brand, Grab harus terus berinovasi dan menunjukkan keunggulan serta perbedaan dibandingkan pesaingnya.